INTERNATIONAL NUCLEAR DATA CENTERS NETWORK AND PROSPECTS OF ITS USE IN NUCLEAR POWER IN BELARUS - Serenkova, I. A.; Pankov, A. A. (Одеські астрономічні публікації, 2019)
We give a brief overview of the existing nuclear data base, and describe the structure of the International Nuclear Data Centres Network. Because the amount of experimental data in nuclear physics is extremely large, the note aims to show the way to modern methods of acquaintance with the char- acteristics of arrays of nuclei through the nuclear data banks accessible through the Web-technologies. In particular, the note describes the methods to extract information on the nuclei and nuclear reactions in nuclear data banks. The data include information on the masses and energies of the nuclei of the separation energy of nucleons and clusters, the spectra of states of nuclei, their spin, parity, isospin, charge and mass radii and densities, information about the shape of the nuclei, the cross sections of nuclear reactions, the decay of unstable nuclei. On the completeness and accuracy of the data depends on radiation and nuclear safety, and environmental acceptability of nuclear installations. Creating a nuclear databases in Belarus will monitor the quality of nuclear data supplied to consumers, and ensure that systems of constants, used in technical projects, the current international standards.